Android malware detection using permission based static analysis - Mohd Ariffin, Noor Afiza; Casinto, Hanna Pungo (Semarak Ilmu Publishing, 2024)
The increase of mobile device enhancement grows. With this development, mobile phones are supporting many programs, and everyone takes advantage of them. Nevertheless, malware applications are increasing more and more so that people can come across lots ofproblems. Android is a mobile operating system that is the most used on smart mobile phones. Because it is the most used and open source, it has been the target of attackers. Android security is related to the permissions allowed by users to the applications. There have been many studies on permission-based Android malware detection. In this study, a permission-based Android malware system is analyzed. Unlike other studies, we propose a permission weight approach. Each of the permissions is given a different score usingthis approach. Then, K-nearest Neighbor (KNN) and Naïve Bayes (NB) algorithms are applied, and the proposed method is compared with the previous studies and the expected experimental results of the proposed approach will be higher.